2004
DOI: 10.1097/01.opx.0000144749.73094.fd
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Accommodation Responses to Stationary Colored Targets

Abstract: In most individuals, viewing multichromatic targets does not increase significantly the variation in accommodative response as compared with broadband black-and-white targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
3
5
0
Order By: Relevance
“…In experiment 1, we also found no effect of LCA on the variance in the accommodative lag. This supports the findings of Atchison et al (2004) who showed that the accommodative response does not switch between accommodating to one colour and then another.…”
Section: Interim Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In experiment 1, we also found no effect of LCA on the variance in the accommodative lag. This supports the findings of Atchison et al (2004) who showed that the accommodative response does not switch between accommodating to one colour and then another.…”
Section: Interim Discussionsupporting
confidence: 91%
“…There were, however, no significant effects of chromaticity separation on the variance in the lag detected in Experiment 1 or in Experiment 2. Atchison et al (2004) compared the variance in the accommodative response to achromatic images and 'multichromatic' images (chromatic Maltise cross on a coloured background). There was no significant difference between the variance in the accommodative response to the multichromatic images and the variance in the response to the achromatic images.…”
Section: Interim Discussionmentioning
confidence: 99%
“…With a black 6/30 Snellen letter target against a uniform monochrome field, the background colour had only minor effects on the fluctuations but there was a systematic change in the mean response with wavelength, associated with the longitudinal chromatic aberration of the eye. Similarly, Atchison et al . found that, in most individuals, steady‐state viewing of multichromatic targets did not significantly increase the variation in accommodative response as compared with that for broadband achromatic targets.…”
Section: Later Workmentioning
confidence: 88%
“…When focusing on the target combined with different colours, the focus may not be very accurate because lights of different wavelengths have their focus points at different locations on the retina. However, various text-background colour combinations on electronic visual displays show no significant difference in the accommodative response, which may stem from the fact that different subjects use different focus strategies [ 23 , 24 ]. Some studies found that light with narrow spectral bandwidth can’t drive accurate accommodation [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%